(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Rao’s choice of Kanthapur TheVillage setting is strategicin view of his Gandhian loyalties. Gandhi locates his politics in the villagesof India where the majority of Indian’s population resides. Rao maintains thesanctity of the village at an ideological level, but permits mobility andchange to heighten the historical significance of the national struggle Gandhiconceptualized. The time when the action of the novel is set is the 1920sand 1930s, the period when Mahatma Gandhi had become the pivotal figure inIndia’s struggle for freedom. Rao treats the history of the freedom movement atthe level of hostility between village folk and the British colonial authorityat a time when colonialism had become intensely heavy-handed in its response tothe Civil Disobedience Movement. Kanthapura is an enchanting story of how theindependence movement becomes a tragic reality in a tiny and secluded villagein South India. The novel has the flavor of an epic as it emerges through theeyes of a delightful old woman who comments with wisdom and humor.